Determinants of Stunting in Children Aged 6-24 Months at Pambusuang Health Centre Working Area, Polewali Mandar Regency, Indonesia - Nurul Ilmi Idrus; Andi Zulkifli; A Arsunan Arsin; Ansariadi; Healthy Hidayanty; Shanti Riskiyani (Medsci Publications, 2023)
Background: Based on the results of the Indonesian Nutrition Status Survey in 2022, the national prevalence of stunting is 21.6% and in the Pambusuang Health Centre working area it is still above the national average of 26.1%. This study aims to determine the determinants that are risk factors for stunting in children aged 6-24 months. Methodology: This research uses a case control study design with a total sample size of 144 consisting of 72 cases and 72 controls selected by systematic random sampling method. Data analysis was carried out using Stata version 14 program. Results: Determinants that are risk factors for stunting are history of LBW (OR=7 with 95% CI=1,453-66,087), pregnancy distance (OR=3.7, with 95% CI=1,698-8,178), knowledge about complementary feeding (OR=4.230 with 95% CI=1,841-10,048) and hand washing with soap habits (OR=5.153 with 95% CI=1,707-18,565). Logistic regression analysis showed that LBW history was the main determinant of stunting in children aged 6-24 months. Conclusions: Risk factors that determine stunting in children aged 6-24 months, including a history of LBW, pregnancy distance, knowledge about complementary feeding and hand washing with soap habits.